An underwater asphalt concrete anti-seepage grouting material and a preparation method and application thereof

CN122464670BActive Publication Date: 2026-10-23NANHUA UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610968610.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-23
Estimated Expiration
2046-07-01

AI Technical Summary

Technical Problem

第一,界面相容性不足与过早破乳风险

Benefits of technology

(1)有效解决了阳离子乳化沥青与水泥相容性差、易提前破乳、流动度经时损失大的技术难题。本发明采用三段式搅拌工艺,先在不含乳化沥青的水溶液中使聚羧酸系减水剂优先吸附于水泥颗粒表面的活性位点,建立稳固的空间位阻分散层,避免减水剂被阳离子沥青颗粒吸附抢夺,从根源上抑制水泥团聚与流动度损失;同时利用非离子型水性环氧树脂与酸性阳离子乳化沥青在预混阶段的范德华力、氢键作用,在不影响沥青胶粒固有双电层静电稳定体系的前提下,于沥青液滴表面构筑受pH驱动的自触发保护壳层,使其在搅拌与注入阶段保持稳定、进入碱性固化环境后随pH跃升而有序脱稳破乳,从而兼顾浆体稳定性与流动性保持能力,满足水下长时间稳定注浆的工程需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122464670B_ABST
    Figure CN122464670B_ABST
Patent Text Reader

Abstract

The application discloses an underwater asphalt concrete anti-seepage grouting material and a preparation method and application thereof. According to mass fractions, the underwater asphalt concrete anti-seepage grouting material comprises 30-50 parts of cationic slow crack emulsified asphalt, 100 parts of inorganic active filler, 0.9-3.7 parts of additive and 31.5-34.5 parts of water; the inorganic active filler comprises 10-20 parts of sulphoaluminate cement and 50-90 parts of ordinary Portland cement; and the additive comprises 0.50-0.55 parts of non-ionic water-based epoxy resin, 0.06-0.09 parts of water-soluble curing agent, 0.09-0.10 parts of sodium gluconate, 0.06-0.13 parts of hydroxypropyl methyl cellulose and 0.23-0.25 parts of polycarboxylate superplasticizer. The grouting material can be widely used in underwater anti-seepage and reinforcement engineering of dam asphalt concrete core wall.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of civil engineering and water conservancy materials technology, specifically to an underwater asphalt concrete anti-seepage grouting material, its preparation method, and its application. Background Technology

[0002] As a core seepage-proof component of dams, asphalt concrete core walls are prone to microcracks or pore defects during long-term service due to factors such as water pressure, temperature fluctuations, and material aging. Developing a grouting material that can adapt to complex underwater conditions, has good compatibility with the asphalt matrix, and possesses long-term durability is of significant engineering value for ensuring the structural safety of water conservancy projects.

[0003] Currently, underwater core wall repair solutions mainly employ cement-based grouts, epoxy resin grouts, or conventional emulsified bitumen-cement-based composite materials. Cement-based grouts provide strength through the mechanical anchoring of cement hydration products; epoxy resin grouts utilize the adhesive properties of polymers to achieve seepage prevention; while conventional emulsified bitumen-cement systems attempt to balance the strength and flexibility of the material through the physical blending of organic and inorganic components. These solutions mostly employ a one-time feeding or a simple two-step mixing process, aiming to achieve preliminary filling and hardening of the grout in the underwater environment.

[0004] However, the aforementioned existing solutions have revealed serious structural and stability problems in practical engineering. These are mainly reflected in: First, there is the risk of insufficient interfacial compatibility and premature demulsification. When using a direct mixing process for emulsified asphalt-cement composite systems, conventional cationic emulsified asphalt, upon contact with the cement slurry, will be affected by high concentrations of alkaline ions (Ca) released during cement hydration. 2+ OH - Rapid neutralization of surface charge triggers instantaneous demulsification, flocculation, and caking, leading to a sharp drop in grout fluidity and making normal pumping and grouting impossible. Although using slow-cracking cationic emulsified asphalt can alleviate the problem of rapid demulsification to some extent, under the strong alkaline environment and high ionic strength of cement, cationic asphalt particles will still adsorb and compete for the anionic water-reducing agent that should act on the cement particles in the system, making it impossible for the cement to be effectively dispersed. In addition, the lack of a stable and effective interfacial protective layer for asphalt particles still makes it difficult to avoid local premature demulsification and loss of fluidity over time, which cannot meet the engineering requirements for long-term stable underwater grouting.

[0005] Secondly, insufficient early structural support and significant consolidation shrinkage easily lead to interfacial debonding and secondary cracking. In underwater high-humidity environments, emulsified asphalt-cement grouting materials are prone to imbalance between physical moisture loss and chemical hydration reactions, resulting in a slow hydration rate and delayed early structural formation. Under high-flow conditions, it is difficult to quickly establish a rigid support framework. Simultaneously, there is a lack of effective shrinkage compensation mechanisms, with consolidation shrinkage typically exceeding 10%. The tensile stress generated by shrinkage is highly concentrated at the interface between the grouting material and the asphalt concrete matrix, easily causing interfacial debonding and secondary cracking, failing to meet the structural stability requirements for long-term seepage prevention of the dam core wall.

[0006] Third, the organic-inorganic interface lacks chemical continuity. Existing materials rely solely on physical adsorption and microscopic interlocking at the interface to achieve bonding. Under the long-term wedging effect of water molecules, the physical anchoring force will rapidly decay, resulting in the reinforcement effect being unable to be maintained in the long term. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of existing technologies and provide an underwater asphalt concrete anti-seepage grouting material, its preparation method, and its application. The underwater asphalt concrete anti-seepage grouting material of this invention possesses excellent fluidity retention, high wet bond strength, and underwater anti-dispersion properties, making it suitable for underwater anti-seepage reinforcement of dam core walls.

[0008] To achieve the above objectives, the technical solution designed by the present invention is as follows: This invention provides an underwater asphalt concrete anti-seepage grouting material, which, by weight, comprises 30-50 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 0.9-3.7 parts admixture, and 31.5-34.5 parts water; The inorganic active filler comprises 10-20 parts of sulfoaluminate cement and 50-90 parts of ordinary silicate cement; The additives include 0.50-0.55 parts of nonionic waterborne epoxy resin, 0.06-0.09 parts of water-soluble curing agent, 0.09-0.10 parts of sodium gluconate, 0.06-0.13 parts of hydroxypropyl methylcellulose and 0.23-0.25 parts of polycarboxylate superplasticizer.

[0009] Furthermore, the additive also includes 2.3 to 2.5 parts of vinyl acetate-ethylene copolymer redispersible latex powder; The particle size of the vinyl acetate-ethylene copolymer redispersible latex powder is 60~120 μm; The viscosity of the nonionic waterborne epoxy resin is 6000~10000 mPa·s, and the water-soluble curing agent is an aliphatic polyamine water-soluble curing agent with a viscosity of 15000~35000 mPa·s. The viscosity of the hydroxypropyl methylcellulose is 200,000 to 300,000 mPa·s.

[0010] Furthermore, the additive also includes 0.06 to 0.12 parts of silane coupling agent KH-560.

[0011] Furthermore, the inorganic active filler also includes 10 to 30 parts of slag powder.

[0012] Furthermore, the underwater asphalt concrete anti-seepage grouting material comprises 40 parts cationic slow-cracking emulsified asphalt, 10 parts sulfoaluminate cement, 60 parts ordinary silicate cement, 30 parts slag powder, 0.522 parts nonionic waterborne epoxy resin, 0.065 parts water-soluble curing agent, 0.096 parts sodium gluconate, 0.072 parts hydroxypropyl methylcellulose, 0.24 parts polycarboxylate superplasticizer, 2.4 parts vinyl acetate-ethylene copolymer redispersible latex powder, 0.12 parts silane coupling agent KH-560, and 31.6 parts water.

[0013] The present invention also provides a method for preparing the underwater asphalt concrete anti-seepage grouting material, comprising the following steps: (1) Weigh out the inorganic active filler, cationic slow-crack emulsified asphalt, nonionic waterborne epoxy resin, water-soluble curing agent, polycarboxylate superplasticizer, hydroxypropyl methylcellulose, sodium gluconate and water according to the above mass proportions; (2) Dissolve polycarboxylate superplasticizer and sodium gluconate in water, then add hydroxypropyl methylcellulose and inorganic active filler, and stir to form cement-based slurry; (3) The epoxy component is obtained by mixing nonionic waterborne epoxy resin and water-soluble curing agent; (4) Take 10-20% of the total mass of cationic slow-crack emulsified asphalt as a diluent, add the epoxy component to the diluent, stir evenly, then add the remaining cationic slow-crack emulsified asphalt and continue stirring to obtain resin-containing emulsified asphalt. (5) Mix resin-containing emulsified asphalt and cement-based slurry, and stir evenly to obtain underwater asphalt concrete anti-seepage grouting material.

[0014] Furthermore, it also includes: in step (5), adding vinyl acetate-ethylene copolymer redispersible latex powder to the mixture of resin-containing emulsified asphalt and cement-based slurry, and stirring evenly to obtain underwater asphalt concrete anti-seepage grouting material.

[0015] Furthermore, it also includes: mixing the silane coupling agent KH-560 with the nonionic waterborne epoxy resin and water-soluble curing agent in the above step (3) to obtain an epoxy component.

[0016] Furthermore, in steps (1) to (5), the stirring speed is 350 to 500 r / min, and the stirring time is 1 to 2 min.

[0017] The present invention also provides an application of the underwater asphalt concrete anti-seepage grouting material described above in the underwater defect repair or anti-seepage reinforcement of the asphalt concrete core wall of a dam.

[0018] The principle of this invention: This invention is based on the excellent compatibility between cationic slow-cracking emulsified asphalt and alkaline cement: cationic slow-cracking emulsified asphalt and alkaline cement (sulfoaluminate cement and ordinary silicate cement) can achieve mild compatibility and slow demulsification, laying the foundation for the stability and orderly solidification of the grout underwater. The inorganic active filler is jointly constructed from sulfoaluminate cement, ordinary silicate cement, and slag powder. Among them, sulfoaluminate cement has a fast hydration rate and rapid early strength development, which can effectively solve the solidification shrinkage problem of high-flowability grouting materials; ordinary silicate cement provides later strength and durability; and slag powder fills the microstructure through the micro-aggregate effect and secondary hydration, improving the system's density and durability.

[0019] Each functional admixture works synergistically through specific mixing processes and feeding sequences: polycarboxylate superplasticizer preferentially adsorbs onto the surface of cement particles, forming a steric hindrance effect and pre-dispersing the cement, preventing it from being adsorbed and encapsulated by cationic asphalt particles and clumping together, thus inhibiting the loss of fluidity over time from the root cause; sodium gluconate retarder adsorbs onto the cement surface, inhibiting early hydration and particle agglomeration, and synergistically with the superplasticizer to prevent the system from rapidly thickening and hardening; water-based epoxy resin is pre-mixed with emulsified asphalt, forming a protective film on the surface of asphalt particles, inhibiting their agglomeration and demulsification, while improving the stability and fluidity of the slurry, achieving mild compatibility between the asphalt phase and the cement phase; the thickener (HPMC) molecular chain, through adsorption and entanglement with cement particles and asphalt particles, constructs a continuous three-dimensional organic network structure inside the slurry, binding the free sedimentation and dispersion migration of solid particles, significantly improving the underwater anti-dispersion properties of the slurry; redispersible latex powder improves interfacial bonding, enhances material toughness and wet bond strength, and ensures a firm bond between the grout and the asphalt concrete core wall. Ultimately, the cationic slow-cracking emulsified asphalt is mildly compatible with cement particles, slowly demulsifies, and forms a continuous asphalt film in the later stage, which intertwines with cement hydration products, giving the material excellent flexibility and impermeability.

[0020] Based on the synergistic effect of the above components, the core working mechanism of this invention can be further summarized into the following four interrelated aspects.

[0021] (1) Coupling self-regulating mechanism of cement hydration and emulsified asphalt demulsification The amine emulsifier of cationic slow-cracking emulsified asphalt (BC-1) remains protonated in acidic to neutral environments (pH<9), and the surface of the asphalt droplets carries a positive charge, making the emulsion stable. When the emulsified asphalt enters alkaline cement paste (pH 12~13), the amine groups gradually deprotonate, the surface charge density decreases, the stability of the emulsion decreases over time, and the asphalt droplets begin to slowly coagulate into a film.

[0022] ① There is a positive feedback coupling between this demulsification process and cement hydration: on the one hand, cement hydration continuously consumes free water, and the Ca in the system... 2+ OH - SO4 2- As plasma concentration increases, it further compresses the double electric layer of asphalt droplets, accelerating the demulsification process. On the other hand, the demulsification of emulsified asphalt releases the water carried in its emulsion phase. This released water is converted into a supplementary water source for the later hydration of cement, promoting the continued growth of hydration products. In low water-cement ratio formulations, emulsified asphalt essentially assumes the functional role of "internal curing".

[0023] ②At the same time, there is also negative feedback regulation in the system: after the asphalt droplets demulsify, a hydrophobic asphalt film is formed on the surface of cement particles, which isolates the direct contact channel between water and cement, thereby inhibiting further hydration reaction; the hydration rate decreases, the ion concentration rises more slowly, the demulsification driving force weakens accordingly, and the asphalt film formation rate also slows down accordingly.

[0024] ③ Positive and negative feedback achieve dynamic equilibrium: During the mixing and injection stage (within the first 30-60 minutes), the emulsion maintains sufficient stability to maintain the fluidity and water resistance of the slurry; during the curing stage after injection (several hours to several days, i.e., curing begins after the underwater asphalt concrete anti-seepage grouting material is injected), hydration and demulsification proceed gradually in synergy, eventually forming a microstructure in which the asphalt film and cement hydration products (CSH gel, ettringite crystals) are interpenetrated. The continuous asphalt film gives the material impermeability and flexibility, while the cement hydration skeleton gives the material strength and durability.

[0025] It is this self-regulating mechanism that enables the grouting material of this invention to solidify normally in an underwater environment with excessive water: although the external water source continuously replenishes the system's moisture and weakens the driving force of "moisture consumption" in the positive feedback, the high concentration of alkaline ions dissolved from the cement can still continuously drive demulsification (its pH driving force does not depend on moisture consumption), and after the asphalt film is formed, it will form a hydrophobic barrier on the outer surface of the solidified body, preventing external water from further penetrating the interior, thereby ensuring the normal progress of core hydration.

[0026] (2) pH self-triggered mechanism of waterborne epoxy resin protective shell During the mixing and injection stage (system pH 7-8, sufficient water content, room temperature), nonionic waterborne epoxy resin droplets are adsorbed onto the surface of cationic emulsified asphalt droplets through intermolecular van der Waals forces and hydrogen bonds, forming a loose epoxy shell layer with a thickness on the submicron scale. This shell layer does not disrupt the inherent electrostatic stability of the asphalt particles' double electric layer, while providing steric hindrance protection, reducing the probability of collisions and coalescence between cationic asphalt droplets, inhibiting agglomeration and demulsification, and significantly improving the long-term retention of slurry fluidity. It should be noted that the viscosity of waterborne epoxy resin (6000-10000 mPa·s) is much higher than that of emulsified asphalt (100-500 mPa·s). If the entire mixture is directly mixed, uneven dispersion is likely to occur due to the viscosity difference. Therefore, a small amount of emulsified asphalt is first used to dilute the epoxy component (premixing the system viscosity to 1000-3000 mPa·s), and then the remaining emulsified asphalt is added. This allows the epoxy component to be quickly and uniformly dispersed and coated on the surface of the asphalt droplets.

[0027] Upon entering the curing stage, three changes occur simultaneously in the system: (i) the pH jumps from neutral to above 12 (ca(OH)2 is dissolved from cement); (ii) free water is continuously consumed by cement hydration, increasing the effective solid content of the epoxy emulsion; and (iii) the exothermic reaction of cement hydration leads to a slight temperature rise in the system. These three factors work synergistically to shift the hydrophilic-lipophilic balance of the epoxy emulsion, lower its cloud point, and cause the outer shell to destabilize and rupture. The released asphalt droplets are exposed to an alkaline environment, thus undergoing normal demulsification and film formation according to the aforementioned self-regulating mechanism. Simultaneously, the epoxy resin in the shell gradually cross-links and cures under the action of an aliphatic polyamine curing agent, forming a microscopic interpenetrating network structure with the asphalt film and cement hydration products, thereby improving the tensile strength and elongation at break of the cured body.

[0028] (3) The covalent bridging mechanism of the organic-inorganic interface of silane coupling agents in the form of "neutral anchoring-alkaline bridging" γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) is a bifunctional coupling agent with a glycidyl group (epoxy group) at one end of the molecule and a trimethoxysilyl group at the other end; the two ends of the molecule react sequentially in different pH environments created by a three-stage process.

[0029] In the near-neutral environment of step 3 (pH 5-7 of emulsified asphalt), the silane hydrolysis rate is extremely slow and the methoxy groups remain intact, allowing sufficient time for the glycidyl groups to react with the epoxy groups in the waterborne epoxy resin or the active amino groups in the curing agent, thereby covalently grafting them into the epoxy resin network and becoming part of the epoxy shell layer of the emulsified asphalt droplets, with their organic ends thus anchored to the organic phase.

[0030] After step 4 enters the alkaline cement paste, the trimethoxysilane terminus of the silane is in the alkali (OH) - Rapid hydrolysis occurs under catalysis: The generated silanol groups (Si-OH) then undergo a condensation reaction with the siloxane groups on the surface of the cement hydration product CSH gel: ≡Si OH+HO Si≡→≡Si O Si≡+H₂O; The reaction proceeds rapidly in an alkaline environment (the silane hydrolysis half-life is only a few minutes at pH>12), covalently anchoring the inorganic end of the silane to the silicon-oxygen network of the cement hydration products. Combining the reactions at both ends, KH-560 establishes a covalent bridge between the organic phase (asphalt film + epoxy cured product) and the inorganic phase (CSH gel): [Asphalt membrane / Epoxy network] CH2 CH(OH) CH2 O (CH2)3 Si( O Si)3[C S H gel].

[0031] This covalent bridge complements the existing non-covalent interfaces of the system, such as physical adsorption and mechanical interlocking: the covalent bonds are not replaced by water molecules, providing water resistance and long-term stability; the combination of physical and mechanical bonds provides initial rapid adhesion and large-area contact. The synergy of these two factors significantly improves underwater wet bonding strength and adhesion retention after immersion.

[0032] It is worth emphasizing that the aforementioned effects of silane coupling agents are highly dependent on their feeding sequence: if added together with cement in step 2, the silane will rapidly hydrolyze and self-condense into polysiloxane microparticles in the alkaline cement slurry (self-polymerization reaction), thus losing its bridging function. It is precisely this three-stage process that creates two distinct pH environments—near-neutral and strongly alkaline—allowing the two functional ends of the silane to complete the orderly reaction of "organic anchoring under neutral conditions → inorganic bridging under alkaline conditions" under their respective optimal conditions. This timing control is a unique coupling effect between the three-stage mixing process and the silane coupling agent, which cannot be achieved in a single-feeding process.

[0033] (4) Dual interface bonding mechanism between grouting material and asphalt concrete matrix The grouting material of this invention, after being injected into the cracks or pores of the asphalt concrete core wall, achieves interfacial bonding with the matrix through a dual mechanism of continuous organic phase bonding and mechanical anchoring of the inorganic phase.

[0034] ① Regarding the continuous organic phase bonding, the asphalt phase precipitated after the emulsified asphalt in the grouting material demulsifies has chemical homology with the original petroleum asphalt binder in the asphalt concrete matrix. At the interface, asphalt molecular chains diffuse and entangle, forming a molecular-scale organic continuous transition layer. This eliminates the weak interfacial layer caused by significant differences in chemical properties between traditional cement-based grouting and the asphalt matrix. This organic continuous layer possesses a thermal expansion coefficient and viscoelastic characteristics similar to the matrix asphalt, allowing it to deform along with the matrix under alternating temperature and structural deformation conditions without detachment or cracking.

[0035] ② Regarding the inorganic phase mechanical anchoring, cement hydration products grow in situ on the inner wall of cracks and in pore spaces: CSH gel penetrates into the micropores and rough pits on the matrix surface to form physical interlocking, and the needle-like ettringite (AFt) crystals (length-to-diameter ratio 5~20) generated by the hydration of sulfoaluminate cement extend into the microcracks of the matrix to provide mechanical anchoring force; as the hydration age increases, the hydration products continuously fill the interface voids, and the anchoring force gradually increases.

[0036] The two mechanisms described above complement each other at different scales and under different operating conditions: the organic continuous layer provides flexible sealing and seepage prevention at the microscale, exhibiting good deformation tracking to low-stress creep and thermal stress; the inorganic anchor provides rigid support and shear strength at the mesoscale, withstanding grouting pressure and water pressure loads. Together, they ensure that the grout-repaired interface simultaneously meets the dual requirements of seepage prevention (the organic sealing layer blocks seepage channels) and structural strength (the inorganic skeleton transfers loads). This is something that pure organic grouting materials (such as epoxy, which only has organic bonding without inorganic anchoring and is not homologous to asphalt) and pure inorganic grouting materials (such as cement grout, which only has inorganic anchoring without organic compatibility) cannot achieve. Furthermore, the covalent bridge established between the organic continuous layer and the inorganic anchor layer by the silane coupling agent prevents water molecules from wedging and splitting along the organic-inorganic interface during long-term underwater service, further enhancing the long-term water resistance and durability of the interface.

[0037] In summary, this invention, through an organic-inorganic composite process and a three-stage mixing process, synergistically solves the problems of poor compatibility, easy dispersion, and rapid loss of fluidity of traditional cement-based slurries and asphalt from three aspects: slurry stability, consolidation shrinkage control, and interfacial chemical continuity. The cationic slow-cracking emulsified asphalt is stably adsorbed with cement particles, and the slurry does not disperse or segregate underwater, which can fully fill cracks and pores. The inorganic cementing system works synergistically with resin and latex powder, giving the material strength, fluidity, and flexibility, as well as strong interfacial bonding, small volume shrinkage, and excellent durability. This meets the requirements of high impermeability and high durability for underwater defect repair and seepage prevention reinforcement of dam asphalt concrete core walls.

[0038] The beneficial effects of this invention are: (1) Effectively solves the technical problems of poor compatibility between cationic emulsified asphalt and cement, easy premature demulsification, and large loss of fluidity over time. The present invention adopts a three-stage mixing process. First, in an aqueous solution without emulsified asphalt, the polycarboxylate superplasticizer is preferentially adsorbed onto the active sites on the surface of cement particles to establish a stable steric dispersion layer, avoiding the superplasticizer being adsorbed and snatched by cationic asphalt particles, thus inhibiting cement agglomeration and fluidity loss from the source. At the same time, the van der Waals force and hydrogen bond effect between nonionic waterborne epoxy resin and acidic cationic emulsified asphalt in the premixing stage are used to construct a pH-driven self-triggering protective shell on the surface of asphalt droplets without affecting the inherent double electric layer electrostatic stability system of asphalt particles. This allows the asphalt droplets to remain stable during the mixing and injection stages and to destabilize and demulsify in an orderly manner as the pH rises after entering the alkaline curing environment. This balances the stability and fluidity retention of the grout, meeting the engineering requirements for long-term stable underwater grouting.

[0039] (2) It significantly inhibits the consolidation shrinkage of the high-fluidity grout, avoiding interface debonding and secondary cracking. This invention uses sulfoaluminate cement and ordinary silicate cement in a specific ratio range. Relying on the characteristics of sulfoaluminate cement, such as fast hydration rate and rapid early strength development, it quickly forms a rigid structural skeleton to constrain the consolidation shrinkage of the matrix. At the same time, the needle-like ettringite crystals generated by its hydration release micro-expansion energy, further assisting in compensating for shrinkage, achieving a consolidation shrinkage rate close to zero, and ensuring the structural stability of the interface between the grout and the asphalt concrete matrix.

[0040] (3) The chemical continuity of the organic-inorganic interface is constructed, which greatly improves the long-term water resistance and durability. This invention utilizes a silane coupling agent to react stepwise in a dynamic pH sequence created by a three-stage process, characterized by "organic anchoring under neutral conditions and inorganic bridging under alkaline conditions". This allows the organic end to be covalently grafted onto the epoxy-asphalt phase, while the inorganic end condenses with cement hydration products to form bonds, thus establishing a covalent bridge between the organic and inorganic phases. This covalent bridging complements the non-covalent bonding of physical adsorption and mechanical interlocking, effectively preventing water molecules from wedging and splitting along the interface during long-term underwater service, and overcoming the defect of rapid decay of the physical anchoring force of existing materials over time.

[0041] (4) The material possesses excellent fluidity retention, underwater anti-dispersion properties, and high wet bond strength. The asphalt phase precipitated after the emulsified asphalt breaks down is chemically homologous with the matrix asphalt, forming a molecular-level organic continuous transition layer at the contact interface, providing flexible sealing and seepage prevention, and can follow the temperature deformation and structural deformation of the matrix without debonding; while the cement hydration products grow in situ on the inner wall of the crack, providing mechanical anchoring and rigid support. The two work together to meet the dual requirements of seepage prevention and structural strength, which is difficult to achieve with pure organic or pure inorganic grouting materials.

[0042] In summary, the grouting material of this invention has good underwater anti-dispersion properties, high wet bond strength, small volume shrinkage, smooth construction, and outstanding seepage prevention and durability. It can be widely used in underwater defect repair and seepage prevention reinforcement of dam asphalt concrete core walls, as well as underwater leak plugging and dam reinforcement in water conservancy projects, and can meet the requirements of high seepage prevention and high durability in hydraulic engineering projects. Attached Figure Description

[0043] Figure 1 Flowchart for the preparation of underwater asphalt concrete anti-seepage grouting material; Figure 2 This diagram shows the water dispersion resistance and underwater spread of the underwater asphalt concrete anti-seepage grouting material. Detailed Implementation

[0044] The present invention will now be described in further detail with reference to specific embodiments, so that those skilled in the art can understand it.

[0045] Unless otherwise specified, all raw materials used in this invention are commercially available. Specifically, the inorganic active filler uses P·O 42.5 grade ordinary silicate cement, SAC 42.5 grade sulfoaluminate cement, and S95 grade slag powder; the cationic slow-cracking emulsified asphalt is type BC-1 with a solid content of 50%; the nonionic waterborne epoxy resin is HS-200 with a viscosity of 6000~10000 mPa·s (25℃); and the water-soluble curing agent is an aliphatic polyamine water-soluble curing agent, type 1012B, with a viscosity of 15000~35000 mPa·s (25℃).

[0046] Example 1 Preparation of underwater asphalt concrete seepage prevention grouting material 1 By mass percentage, the underwater asphalt concrete anti-seepage grouting material 1 in this embodiment comprises: 40 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 3.475 parts admixture, and 34 parts water. The inorganic active filler includes 10 parts sulfoaluminate cement and 90 parts ordinary silicate cement, with sulfoaluminate cement accounting for 10% of the total mass of the inorganic active filler. The admixture includes 0.522 parts nonionic waterborne epoxy resin, 0.085 parts water-soluble curing agent, 0.096 parts sodium gluconate, 0.072 parts hydroxypropyl methylcellulose (HPMC), 0.24 parts polycarboxylate superplasticizer, 2.4 parts vinyl acetate-ethylene copolymer redispersible latex powder, and 0.06 parts silane coupling agent KH-560. The viscosity of HPMC is 250,000 mPa·s, and the average particle size of the vinyl acetate-ethylene copolymer redispersible latex powder is 60 μm.

[0047] Combination Figure 1 As shown, the preparation process of the seepage-proof grouting material in this embodiment is as follows: (1) Weigh out the following components according to the above mass proportions: sulfoaluminate cement, ordinary silicate cement, cationic slow-crack emulsified asphalt, nonionic waterborne epoxy resin, water-soluble curing agent, polycarboxylic acid water-reducing agent, sodium gluconate, hydroxypropyl methylcellulose HPMC, vinyl acetate-ethylene copolymer redispersible latex powder, silane coupling agent KH-560 and water.

[0048] (2) Mix polycarboxylate superplasticizer, sodium gluconate (retarder) and water, stir to dissolve, then add HPMC, sulfoaluminate cement and ordinary silicate cement, stir at low speed for 1.5 min at 350 r / min to form a uniform cement-based slurry.

[0049] (3) The nonionic waterborne epoxy resin, water-soluble curing agent and silane coupling agent KH-560 are premixed evenly to form an epoxy component.

[0050] (4) Take 15% (6 parts) of the total mass of cationic slow-crack emulsified asphalt as a dilution medium, slowly add the epoxy component to the dilution medium, stir at 350 r / min for 1 min to make it evenly distributed, then add the remaining 85% of cationic slow-crack emulsified asphalt (34 parts) and continue stirring for 1 min to obtain resin-containing emulsified asphalt.

[0051] (5) Add resin-containing emulsified asphalt to the cement-based grout, and add vinyl acetate-ethylene copolymer redispersible latex powder. Continue stirring at 350 r / min for 2 min until the mixture is homogeneous, thus obtaining underwater asphalt concrete anti-seepage grouting material 1. Figure 2 As shown.

[0052] Example 2 Preparation of underwater asphalt concrete anti-seepage grouting material 2 By mass percentage, the underwater asphalt concrete anti-seepage grouting material 2 in this embodiment comprises: 30 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 3.273 parts admixture, and 34.45 parts water. The inorganic active filler includes 10 parts sulfoaluminate cement and 90 parts ordinary silicate cement, with sulfoaluminate cement accounting for 10% of the total mass of the inorganic active filler. The admixture includes 0.5 parts nonionic waterborne epoxy resin, 0.082 parts water-soluble curing agent, 0.092 parts sodium gluconate, 0.069 parts hydroxypropyl methylcellulose (HPMC), 0.23 parts polycarboxylate superplasticizer, and 2.3 parts vinyl acetate-ethylene copolymer redispersible latex powder. The HPMC has a viscosity of 250,000 mPa·s, and the average particle size of the vinyl acetate-ethylene copolymer redispersible latex powder is 60 μm.

[0053] The preparation process steps in this embodiment are the same as in Embodiment 1, except that: (1) In step 4: Take 10% (3 parts) of the total mass of cationic slow-crack emulsified asphalt as a dilution medium, slowly add the epoxy component to the dilution medium, stir at 350 r / min for 1 min to make it evenly distributed, then add the remaining 90% of cationic slow-crack emulsified asphalt (27 parts) and continue stirring for 1 min to obtain resin-containing emulsified asphalt.

[0054] (2) No silane coupling agent KH-560 is added.

[0055] Example 3 Preparation of underwater asphalt concrete anti-seepage grouting material 3 By mass percentage, the underwater asphalt concrete anti-seepage grouting material 3 in this embodiment comprises: 50 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 3.669 parts admixture, and 33.75 parts water. The inorganic active filler includes 10 parts sulfoaluminate cement and 90 parts ordinary silicate cement, with sulfoaluminate cement accounting for 10% of the total mass of the inorganic active filler. The admixture includes: 0.543 parts nonionic waterborne epoxy resin, 0.088 parts water-soluble curing agent, 0.1 parts sodium gluconate, 0.125 parts hydroxypropyl methylcellulose (HPMC), 0.25 parts polycarboxylate superplasticizer, 2.5 parts vinyl acetate-ethylene copolymer redispersible latex powder, and 0.063 parts silane coupling agent KH-560. The viscosity of HPMC is 250,000 mPa·s, and the average particle size of the vinyl acetate-ethylene copolymer redispersible latex powder is 60 μm.

[0056] The preparation process steps in this embodiment are the same as in Embodiment 1, except that: In step 4: Take 20% (10 parts) of the total mass of cationic slow-cracking emulsified asphalt as the dilution medium, slowly add the epoxy component to the dilution medium, stir at 350 r / min for 1 min to make it evenly distributed, then add the remaining 80% of the cationic slow-cracking emulsified asphalt (40 parts) and continue stirring for 1 min to obtain resin-containing emulsified asphalt.

[0057] Example 4 Preparation of underwater asphalt concrete seepage prevention grouting material 4 By mass percentage, the underwater asphalt concrete anti-seepage grouting material 4 in this embodiment includes: 40 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 3.528 parts admixture and 31.6 parts water. The inorganic active filler includes 10 parts sulfoaluminate cement, 80 parts ordinary Portland cement and 10 parts S95 grade slag powder. The sulfoaluminate cement accounts for 10% of the total mass of the inorganic active filler and the slag powder accounts for 10% of the total mass of the inorganic active filler. The additives include 0.522 parts of nonionic waterborne epoxy resin, 0.078 parts of water-soluble curing agent, 0.096 parts of sodium gluconate, 0.072 parts of hydroxypropyl methylcellulose (HPMC), 0.24 parts of polycarboxylate superplasticizer, 2.4 parts of vinyl acetate-ethylene copolymer redispersible latex powder, and 0.12 parts of silane coupling agent KH-560. The viscosity of HPMC is 250,000 mPa·s, and the average particle size of vinyl acetate-ethylene copolymer redispersible latex powder is 60 μm.

[0058] The preparation process steps in this embodiment are the same as in Embodiment 1.

[0059] Example 5 Preparation of underwater asphalt concrete seepage prevention grouting material 5 By mass percentage, the underwater asphalt concrete anti-seepage grouting material 5 in this embodiment comprises: 40 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 3.535 parts admixture, and 31.6 parts water. The inorganic active filler includes 10 parts sulfoaluminate cement and 90 parts ordinary silicate cement, with sulfoaluminate cement accounting for 10% of the total mass of the inorganic active filler. The admixture includes 0.522 parts nonionic waterborne epoxy resin, 0.085 parts water-soluble curing agent, 0.096 parts sodium gluconate, 0.072 parts hydroxypropyl methylcellulose (HPMC), 0.24 parts polycarboxylate superplasticizer, 2.4 parts vinyl acetate-ethylene copolymer redispersible latex powder, and 0.12 parts silane coupling agent KH-560. The viscosity of HPMC is 300,000 mPa·s, and the average particle size of the vinyl acetate-ethylene copolymer redispersible latex powder is 120 μm.

[0060] The preparation process steps in this embodiment are the same as in Embodiment 1.

[0061] Example 6 Preparation of underwater asphalt concrete seepage prevention grouting material 6 By mass percentage, the underwater asphalt concrete anti-seepage grouting material 6 in this embodiment includes: 40 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 3.515 parts admixture and 31.6 parts water. The inorganic active filler includes 10 parts sulfoaluminate cement, 60 parts ordinary Portland cement and 30 parts S95 grade slag powder. The sulfoaluminate cement accounts for 10% of the total mass of the inorganic active filler and the slag powder accounts for 30% of the total mass of the inorganic active filler. The additives include 0.522 parts of nonionic waterborne epoxy resin, 0.065 parts of water-soluble curing agent, 0.096 parts of sodium gluconate, 0.072 parts of hydroxypropyl methylcellulose (HPMC), 0.24 parts of polycarboxylate superplasticizer, 2.4 parts of vinyl acetate-ethylene copolymer redispersible latex powder, and 0.12 parts of silane coupling agent KH-560. The viscosity of HPMC is 250,000 mPa·s, and the average particle size of vinyl acetate-ethylene copolymer redispersible latex powder is 60 μm.

[0062] The preparation process steps in this embodiment are the same as in Embodiment 1.

[0063] Example 7 Preparation of underwater asphalt concrete seepage prevention grouting material 7 By mass percentage, the underwater asphalt concrete anti-seepage grouting material 7 in this embodiment comprises: 40 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 3.535 parts admixture, and 31.6 parts water. The inorganic active filler includes 10 parts sulfoaluminate cement and 90 parts ordinary silicate cement, with sulfoaluminate cement accounting for 10% of the total mass of the inorganic active filler. The admixture includes 0.522 parts nonionic waterborne epoxy resin, 0.085 parts water-soluble curing agent, 0.096 parts sodium gluconate, 0.072 parts hydroxypropyl methylcellulose (HPMC), 0.24 parts polycarboxylate superplasticizer, 2.4 parts vinyl acetate-ethylene copolymer redispersible latex powder, and 0.12 parts silane coupling agent KH-560. The viscosity of HPMC is 250,000 mPa·s, and the average particle size of the vinyl acetate-ethylene copolymer redispersible latex powder is 60 μm.

[0064] The preparation process steps in this embodiment are the same as in embodiment 1, except that in steps 2, 4 and 5, the stirring speed is uniformly adjusted to 500 r / min.

[0065] Example 8 Preparation of underwater asphalt concrete seepage prevention grouting material 8 This embodiment employs a cross-combination of high-dosage slag powder and high-dosage sulfoaluminate cement. By mass, the underwater asphalt concrete anti-seepage grouting material 8 in this embodiment comprises: 40 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 3.522 parts admixture, and 31.6 parts water. The inorganic active filler includes 20 parts sulfoaluminate cement, 50 parts ordinary Portland cement, and 30 parts S95 grade slag powder. The sulfoaluminate cement accounts for 20% of the total mass of the inorganic active filler, and the S95 grade slag powder accounts for 30%. The additives include 0.522 parts of nonionic waterborne epoxy resin, 0.072 parts of water-soluble curing agent, 0.096 parts of sodium gluconate, 0.072 parts of hydroxypropyl methylcellulose (HPMC), 0.24 parts of polycarboxylate superplasticizer, 2.4 parts of vinyl acetate-ethylene copolymer redispersible latex powder, and 0.12 parts of silane coupling agent KH-560. The viscosity of HPMC is 250,000 mPa·s, and the particle size of vinyl acetate-ethylene copolymer redispersible latex powder is 60 μm.

[0066] The preparation process steps in this embodiment are the same as in Embodiment 1. The high-content slag powder is uniformly dispersed in the system by three-stage stirring.

[0067] Example 9 Preparation of underwater asphalt concrete anti-seepage grouting material 9 By weight, the underwater asphalt concrete anti-seepage grouting material 9 in this embodiment comprises: 30 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 0.959 parts admixture, and 34.45 parts water. The inorganic active filler includes 20 parts sulfoaluminate cement, 50 parts ordinary silicate cement, and 30 parts S95 slag powder. Ssulfoaluminate cement accounts for 20% of the total mass of the inorganic active filler, and S95 slag powder accounts for 30%. The admixture includes 0.5 parts nonionic waterborne epoxy resin, 0.068 parts water-soluble curing agent, 0.092 parts sodium gluconate, 0.069 parts hydroxypropyl methylcellulose (HPMC), and 0.23 parts polycarboxylate superplasticizer. The viscosity of HPMC is 250,000 mPa·s.

[0068] The preparation steps in this embodiment are the same as in Embodiment 1, except that: (1) Redispersible latex powder without the addition of silane coupling agent KH-560 and vinyl acetate-ethylene copolymer.

[0069] (2) In step 4: Take 10% (3 parts) of the total mass of cationic slow-crack emulsified asphalt as a dilution medium, slowly add the epoxy component to the dilution medium, stir at 350 r / min for 1 min to make it evenly distributed, then add the remaining 90% of cationic slow-crack emulsified asphalt (27 parts) and continue stirring for 1 min to obtain resin-containing emulsified asphalt.

[0070] Example 10 Preparation of underwater asphalt concrete seepage prevention grouting material 10 By mass percentage, the underwater asphalt concrete anti-seepage grouting material 10 in this embodiment includes: 50 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 3.656 parts admixture and 33.75 parts water. The inorganic active filler includes 20 parts sulfoaluminate cement, 50 parts ordinary Portland cement and 30 parts slag powder. The sulfoaluminate cement accounts for 20% of the total mass of the inorganic active filler, and the S95 grade slag powder accounts for 30% of the total mass of the inorganic active filler. The additives include 0.543 parts of nonionic waterborne epoxy resin, 0.075 parts of water-soluble curing agent, 0.1 parts of sodium gluconate, 0.125 parts of hydroxypropyl methylcellulose (HPMC), 0.25 parts of polycarboxylate superplasticizer, 2.5 parts of vinyl acetate-ethylene copolymer redispersible latex powder, and 0.063 parts of silane coupling agent KH-560. The viscosity of HPMC is 200,000 mPa·s, and the particle size of vinyl acetate-ethylene copolymer redispersible latex powder is 60 μm.

[0071] The preparation process steps in this embodiment are the same as in Embodiment 1.

[0072] Comparative Example 1 Preparation of underwater asphalt concrete seepage prevention grouting material D1 The composition and dosage of the underwater asphalt concrete anti-seepage grouting material D1 in this comparative example are the same as in Example 1. Its preparation method adopts the conventional one-time feeding method: the polycarboxylate superplasticizer, retarder sodium gluconate, hydroxypropyl methylcellulose, vinyl acetate-ethylene copolymer redispersible latex powder, and silane coupling agent KH-560 are dissolved and dispersed in water in one step. Then, inorganic active filler, cationic slow-cracking emulsified asphalt, nonionic waterborne epoxy resin, and water-soluble curing agent are added, and the mixture is directly stirred at 350 r / min for 3 min. This comparative example is used to demonstrate the necessity of the three-stage mixing process.

[0073] Comparative Example 2 Preparation of D2 underwater asphalt concrete seepage prevention grouting material The underwater asphalt concrete anti-seepage grouting material D2 in this comparative example is the same as in Example 1, except that it does not contain water-based epoxy resin and water-soluble curing agent. This comparative example is used to demonstrate the protective and synergistic stabilizing effect of water-based epoxy resin on cationic emulsified asphalt.

[0074] Comparative Example 3 Preparation of D3 underwater asphalt concrete seepage prevention grouting material The underwater asphalt concrete anti-seepage grouting material D3 in this comparative example is the same as in Example 1, except that all sulfoaluminate cement is replaced with ordinary silicate cement (i.e., all inorganic active fillers are ordinary silicate cement). This comparative example is used to demonstrate the limiting effect of sulfoaluminate cement on consolidation shrinkage.

[0075] Comparative Example 4 Preparation of D4, an underwater asphalt concrete seepage prevention grouting material The underwater asphalt concrete anti-seepage grouting material D4 in this comparative example is the same as in Example 1, except that the nonionic waterborne epoxy resin is replaced with anionic waterborne epoxy resin STW602, with a viscosity of 6000~10000 mPa·s (25℃), and the corresponding water-soluble curing agent is replaced with an aliphatic polyamine water-soluble curing agent, model STW703B, with a viscosity of 15000~35000 mPa·s (25℃). This comparative example is used to demonstrate the importance of the polarity matching (nonionic or cationic) of the admixtures for the stability of the system.

[0076] Comparative Example 5 Preparation of D5 underwater asphalt concrete seepage prevention grouting material The underwater asphalt concrete anti-seepage grouting material D5 in this comparative example is the same as in Example 1, except that the nonionic waterborne epoxy resin is replaced with cationic waterborne epoxy resin CY-EP60, with a viscosity of 6000~10000 mPa·s (25℃), and the corresponding water-soluble curing agent is replaced with a modified aliphatic polyamine water-soluble curing agent, model CY-C90, with a viscosity of 15000~35000 mPa·s (25℃). This comparative example is used to demonstrate the importance of the polarity matching (nonionic or cationic) of the admixtures for the stability of the system.

[0077] Comparative Example 6 Preparation of D6 underwater asphalt concrete seepage prevention grouting material This comparative example uses the same underwater asphalt concrete anti-seepage grouting material D6 as in Example 1, except that in step 2, the silane coupling agent KH-560 is added directly to the water along with the polycarboxylate superplasticizer and sodium gluconate (retarder), instead of being premixed with the nonionic waterborne epoxy resin and water-soluble curing agent in step 3. This comparative example is used to demonstrate the effect of the timing of silane coupling agent addition on the chemical bridging effect.

[0078] Comparative Example 7 Preparation of D7 underwater asphalt concrete seepage prevention grouting material By mass percentage, the underwater asphalt concrete anti-seepage grouting material D7 in this comparative example comprises: 40 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 3.529 parts admixture, and 31.6 parts water. The inorganic active filler includes 6 parts sulfoaluminate cement, 90 parts ordinary silicate cement, and 4 parts S95 slag powder. Sulfoaluminate cement accounts for 6% of the total mass of the inorganic active filler, and S95 slag powder accounts for 4%. The admixture includes 0.522 parts nonionic waterborne epoxy resin, 0.08 parts water-soluble curing agent, 0.096 parts sodium gluconate, 0.072 parts hydroxypropyl methylcellulose (HPMC), 0.24 parts polycarboxylate superplasticizer, 2.4 parts vinyl acetate-ethylene copolymer redispersible latex powder, and 0.12 parts silane coupling agent KH-560.

[0079] The preparation steps for this comparative example are the same as in Example 1. This comparative example is used to demonstrate the technical effect when the proportion of sulfoaluminate cement is below a critical value.

[0080] Performance testing 1. The performance of underwater asphalt concrete anti-seepage grouting materials 1-10 prepared in Examples 1-10 and underwater asphalt concrete anti-seepage grouting materials D1-D7 prepared in Comparative Examples 1-7 were tested, and the results are shown in Table 1.

[0081] Table 1 Performance Test Results Comparing Example 1 and Comparative Example 1, it can be seen that the three-stage mixing process achieves orderly interaction of components at the physicochemical level. Example 1 first mixes a polycarboxylate superplasticizer and inorganic active filler in an aqueous solution of cationic slow-cracking emulsified asphalt, allowing the polycarboxylate superplasticizer molecules to preferentially adsorb onto calcium ion sites on the surface of cement particles, thereby establishing a stable steric barrier. In contrast, Comparative Example 1 uses a single-stage mixing process, where the cationic slow-cracking emulsified asphalt rapidly neutralizes the negatively charged superplasticizer, causing charge imbalance and violent agglomeration of cement particles, resulting in a much higher fluidity loss rate than in Example 1.

[0082] Comparing Example 1 and Comparative Example 2, it is evident that the nonionic waterborne epoxy resin plays a crucial role in maintaining system stability and improving fluidity retention. In the second stage of the three-stage process, epoxy resin droplets, relying on electrostatic interactions, are directionally adsorbed onto the surface of cationic slow-cracking emulsified asphalt particles, forming a submicron-level steric hindrance shell layer. This protective layer isolates the cationic slow-cracking emulsified asphalt particles, preventing their aggregation, and effectively blocks direct electrostatic attraction between asphalt and cement particles, preventing asphalt particles from adsorbing and competing for anionic water-reducing agents in the system. Simultaneously, without sacrificing slurry stability, it significantly improves the system's fluidity and retention over time, inhibiting premature demulsification of the cationic slow-cracking emulsified asphalt in the strongly alkaline environment of cement. Consequently, the fluidity retention of Example 1 is significantly superior to that of Comparative Example 2, which did not contain nonionic waterborne epoxy resin.

[0083] Comparing the performance data of Example 1, Comparative Example 4, and Comparative Example 5, it can be seen that the charge polarity of epoxy resin only changes the rheological stability of the grout over time, and has no significant impact on the bulk properties of the hardened matrix, such as compressive strength, shrinkage, and interfacial adhesion. Anionic aqueous epoxy resin undergoes electrostatic neutralization with cationic emulsified asphalt, disrupting the double electric layer structure on the surface of the asphalt particles. This causes them to lose electrostatic repulsion and rapidly collide and agglomerate, ultimately resulting in a significant decrease in grout fluidity within a short period, with the fluidity loss rate surging from 32.5% to 72.8% in 20 minutes. Cationic aqueous epoxy resin is electrostatically repelled by cationic emulsified asphalt, failing to coat the asphalt particles, resulting in severe flocculation and complete loss of workability. In contrast, nonionic aqueous epoxy resin has no charge conflict and can form a protective organic film on the surface of asphalt particles, controlling fluidity loss to a low level. It balances both construction rheological properties and the comprehensive performance of the hardened material, making it the optimal choice for cationic emulsified asphalt grouting systems.

[0084] Comparing Example 1 and Comparative Example 6, it can be seen that the technical effect of the silane coupling agent is highly dependent on the dynamic pH environment created by the three-stage process. In Example 1, the glycidyl groups of the silane are first anchored to the organic end with the epoxy resin or asphalt phase in the neutral environment of step 3, and then the condensation reaction between the silanol groups and the cement hydration products is triggered in the alkaline environment of step 4. In Comparative Example 6, the silane coupling agent is directly added to the alkaline water in step 2, which causes it to undergo a rapid self-condensation reaction under alkali catalysis and lose its bridging activity. Therefore, its final wet bond strength and strength retention rate will be significantly lower than those of Example 1.

[0085] Comparing Examples 1-10 with Comparative Examples 3 and 7, it is evident that the dosage of sulfoaluminate cement directly determines the material's ability to suppress shrinkage stress. Examples 1-10 controlled the sulfoaluminate cement dosage within a specific range of 10-20% of the total mass of the inorganic active filler. This relied on the rapid hydration rate and early strength development of sulfoaluminate cement to quickly form a rigid structural framework. The framework's constraint effect limited the matrix consolidation shrinkage, ultimately achieving a consolidation shrinkage rate close to 0.0%. Comparative Example 3, lacking sulfoaluminate cement, failed to form effective structural support in the early stages, resulting in a significant increase in consolidation shrinkage to 12.4%. Comparative Example 7, with a dosage below the aforementioned specific range, suffered from insufficient sulfoaluminate cement, leading to delayed early structural framework formation and insufficient constraint, still exhibiting significant shrinkage. This clearly demonstrates that the specific 10-20% dosage range has significant critical technical value in ensuring rapid early framework formation, suppressing consolidation shrinkage, and preventing debonding at the underwater grouting interface.

[0086] Comparing Examples 1, 8, and 4, it is evident that appropriately increasing the content of slag powder (S95 grade) (from 0% to 30% of the total mass of inorganic active filler) can further fill the interfacial gaps between the asphalt film and cement paste by utilizing its micro-aggregate effect and secondary hydration. Combined with a high dose of silane coupling agent, Example 8 exhibited excellent 28-day underwater strength retention (93%), demonstrating a significant synergistic strengthening effect between chemical bridging and physical filling in complex multi-component systems.

[0087] Example 9 exhibited an initial flowability of 186 mm, a 20-minute flowability loss rate of 38.5%, good underwater anti-dispersion properties, a consolidation shrinkage rate of 0.1%, and a 28-day wet bond strength of 0.7 MPa. Comparing with Example 1, it is evident that even with nonionic waterborne epoxy resin and without the addition of silane coupling agents and redispersible latex powder, the system still maintains good workability and anti-dispersion properties, although the wet bond strength is significantly reduced. This verifies the crucial contribution of silane coupling agents and redispersible latex powder to interfacial bonding performance. Simultaneously, the slurry retains pourability even with reduced total water content, further demonstrating the advantages of the three-stage mixing process in controlling water-reducing agent adsorption and optimizing slurry rheology.

[0088] The verification results from the high-content emulsified asphalt and high-content sulfoaluminate cement system in Example 10 show that, in the early stages, the system relies on the rapid hydration of sulfoaluminate cement to form a rigid structural framework, which plays a basic role in restraining shrinkage and stabilizing the shrinkage rate at 0.0%. This further confirms that the sulfoaluminate cement (SAC) to ordinary Portland cement (OPC) ratio range defined in this invention has good universality and reliability in emulsified asphalt systems with different contents, providing flexibility in formula adjustment to meet the grouting requirements of cracks of different widths in the dam core wall and broadening the engineering application range of the material.

[0089] All other parts not described in detail are existing technologies. Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. An underwater asphalt concrete anti-seepage grouting material, characterized in that: By weight, the underwater asphalt concrete anti-seepage grouting material comprises 30-50 parts cationic slow-cracking emulsified asphalt, 100 parts inorganic active filler, 0.9-3.7 parts admixture, and 31.5-34.5 parts water; The inorganic active filler comprises 10-20 parts of sulfoaluminate cement and 50-90 parts of ordinary silicate cement; The additives include 0.50-0.55 parts of nonionic waterborne epoxy resin, 0.06-0.09 parts of water-soluble curing agent, 0.09-0.10 parts of sodium gluconate, 0.06-0.13 parts of hydroxypropyl methylcellulose and 0.23-0.25 parts of polycarboxylate superplasticizer; The additive also includes 2.3 to 2.5 parts of vinyl acetate-ethylene copolymer redispersible latex powder; The additive also includes 0.06 to 0.12 parts of silane coupling agent KH-560; The underwater asphalt concrete anti-seepage grouting material is prepared by a method including the following steps: (1) Weigh out the inorganic active filler, cationic slow-crack emulsified asphalt, nonionic waterborne epoxy resin, water-soluble curing agent, polycarboxylic acid water-reducing agent, hydroxypropyl methylcellulose, sodium gluconate, water, silane coupling agent KH-560 and vinyl acetate-ethylene copolymer redispersible latex powder according to the above mass parts; (2) Dissolve polycarboxylate superplasticizer and sodium gluconate in water, then add hydroxypropyl methylcellulose and inorganic active filler, and stir to form cement-based slurry; (3) The epoxy component is obtained by mixing silane coupling agent KH-560, nonionic waterborne epoxy resin and water-soluble curing agent; (4) Take 10-20% of the total mass of cationic slow-crack emulsified asphalt as a diluent, add the epoxy component to the diluent, stir evenly, then add the remaining cationic slow-crack emulsified asphalt and continue stirring to obtain resin-containing emulsified asphalt. (5) Mix resin-containing emulsified asphalt and cement-based slurry, add vinyl acetate-ethylene copolymer redispersible latex powder, and stir evenly to obtain underwater asphalt concrete anti-seepage grouting material; In steps (2) to (5), the stirring speed is 350 to 500 r / min and the stirring time is 1 to 2 min.

2. The underwater asphalt concrete anti-seepage grouting material according to claim 1, characterized in that: The particle size of the vinyl acetate-ethylene copolymer redispersible latex powder is 60~120 μm; The viscosity of the nonionic waterborne epoxy resin is 6000~10000 mPa·s, and the water-soluble curing agent is an aliphatic polyamine water-soluble curing agent with a viscosity of 15000~35000 mPa·s. The viscosity of the hydroxypropyl methylcellulose is 200,000 to 300,000 mPa·s.

3. The underwater asphalt concrete anti-seepage grouting material according to claim 1, characterized in that: The inorganic active filler also includes 10-30 parts of slag powder.

4. The underwater asphalt concrete anti-seepage grouting material according to claim 3, characterized in that: The underwater asphalt concrete anti-seepage grouting material comprises 40 parts cationic slow-cracking emulsified asphalt, 10 parts sulfoaluminate cement, 60 parts ordinary silicate cement, 30 parts slag powder, 0.522 parts nonionic waterborne epoxy resin, 0.065 parts water-soluble curing agent, 0.096 parts sodium gluconate, 0.072 parts hydroxypropyl methylcellulose, 0.24 parts polycarboxylate superplasticizer, 2.4 parts vinyl acetate-ethylene copolymer redispersible latex powder, 0.12 parts silane coupling agent KH-560, and 31.6 parts water.

5. The application of the underwater asphalt concrete anti-seepage grouting material according to any one of claims 1 to 4 in the underwater defect repair or anti-seepage reinforcement of the asphalt concrete core wall of a dam.

Citation Information

Patent Citations

  • Asphalt pavement crack rapid repair material with low shrinkage and high bonding strength and preparation method thereof

    CN105948664A

  • Waterborne epoxy resin modified emulsified asphalt cold patch material for rapid road repair and preparation method thereof

    CN111606605A